The sixth sense - Marshall, Frank; Kennedy Kathleen; Shyamalam, M. Night (USA: Buena Vista Home Entertaiment [production company] ; Kuala Lumpur : Berjaya HVN [distributor], 1998)
Hollywood superstar Bruce Willis brings a powerful presence to an edge-of-your seat supernatural thriller that critics are calling one of the year's best movies
Executive producer, Sam Merger ; music, James Newton Howard
Cast: Bruce Willis, Haley Joel Osment, Tone Collette, Olivia Williams
Keywords: Supernatural in motion pictures; Suspense in motion pictures